Model of Good Corporate Governance Implementation for Medium, Small and Micro Business Enterprises on East Java - Panggah Setiyono, Wisnu; Ambarwati Sukmono, Rita; Fediyanto, Niko (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the fit model of the implementation of good corporate governance on MSME’s of East Java province. This study uses quantitative methods with questionnaires as a data collection tool that is distributed to respondents. The population of this study is all MSME’s in Sidoarjo, Surabaya, Malang and Madiun. The sampling technique used a purposive sampling technique so that it gets 150 respondents especially for medium entreprises. The data were analyzed using Structural Equation Modeling (SEM) with AMOS program version 21.0. This research uses an exogenous variable (X) that is good corporate governance implementation and preparation of the financial statement, and endogenous variable (Y) business performance. The results of this study with SEM analysis indicate that good corporate Governance has a significant effect on business performance. Whereas the preparation of financial statements has no significant impact on business performance